Coherent spike-wave oscillations in the cortex and subthalamic nucleus of the freely moving rat. - Magill, P; Sharott, A; Harnack, D; Kupsch, A; Meissner, W; Brown, P (2005)
The basal ganglia play a critical role in controlling seizures in animal models of idiopathic non-convulsive (absence) epilepsy. Inappropriate output from the substantia nigra pars reticulata (SNr) is known to exacerbate seizures, but the precise neuronal mechanisms underlying abnormal activity in SNr remain unclear. To test the hypothesis that cortical spike-wave oscillations, often considered indicative of absence seizures, propagate to the subthalamic nucleus, an important afferent of SNr, we simultaneously recorded local field potentials from the frontal cortex and subthalamic nucleus of freely moving rats. Spontaneous spike-wave oscillations in cortex (mean dominant frequency of 7.4 Hz) were associated with similar oscillations in the subthalamic nucleus (mean of 7.9 Hz). The power of oscillations at 5-9 Hz was significantly higher during spike-wave activity as compared with rest periods without this activity. Importantly, spike-wave oscillations in cortex and subthalamic nucleus were significantly coherent across a range of frequencies (3-40 Hz), and the dominant (7-8 Hz) oscillatory activity in the subthalamic nucleus typically followed that in cortex with a small time lag (mean of 2.7 ms). In conclusion, these data suggest that ensembles of subthalamic nucleus neurons are rapidly recruited into oscillations during cortical spike-wave activity, thus adding further weight to the importance of the subthalamic nucleus in absence epilepsy. An increase in synchronous oscillatory input from the subthalamic nucleus could thus partly underlie the expression of pathological activity in SNr that could, in turn, aggravate seizures. Finally, these findings also reiterate the importance of oscillations in these circuits in normal behaviour.